Civilization values are the most crucial ethics of societies. - پرۆفیسۆرى یاریدەدەر دکتۆر ئيدريس عەبدولال مستەفا (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
They came from the Heavenly religion and they are accepted by people’s mind. Moreover, civilization values are the source of happiness and they are a main tool for developing societies. In contrast, people face a bad life, when they drop the civilized values and take negative steps towards them. Kurdish literature with its 400 years age was created by Mullah Jaziri, Ahmad Khani, Nali, Mawlawi, Mahwy and others. All of the mentioned names were Mullah and experts in Islam. Therefore, Kurdish culture has a great literature. Kurdish literature is the reflection of Islamic civilization value and it is a developed form of human’s life and happiness. The following points are the results of the current study: 1- Civilization values: they are ethic values which have a high ethic level. They come from religion and are accepted by the human’ mind. 2- A great part of the Kurdish literature is ethic literature and vital civilization values. 3- Each one of knowing Allah, greatness and smallness, justice, freedom, seeking knowledge, hospitality, honesty, working and mother’s rights, is dealt with very much. Additionally, people are encouraged for keeping them. 4- If people follow these civilization values, societies will take positive steps and develop. But, if people do not follow them, the result will be different and opposed.